Draft Annual Plan 1999-2002 Volume III Statements VIII to XVI Government of Uttar Pradesh - Planning Commission (Planning Commission, 1999)
Plant Protection Scheme for control of pest and diseases of Agricultural Importance. Subsidy on High Yielding Varieties of Seed Exchange Programme in Tribal Blocks. Scheme for Intensive and Multiple cropping(DS). Special Programme of Rice Production (DS+CSS). Distribution of subsidy in remaining districts like SEPP for crop production. Integrated Cereal Development Programme (CSS) Wheat. Integrated cereal development programme (DS,CSS) coarse cereal.
Statements VIII to XVI
Government of Uttar Pradesh